Type 2 diabetic neuropathy with special reference to mitochondrial role and its effective management - Kasinathan, Devi; Marimuthu, Prabhu Narayanan; Ramar, Manikandan (Research in Biotechnology, 2013)
Diabetic neuropathy denotes to a group of nerve disorders caused by diabetes. It may occur in both type 1 and type 2 diabetes patients. Mitochondria are essential for energy production as well as intermediary metabolism and equally important in the action of insulin on its targeted tissue. Recently, mitochondrial dysfunctions have been recognized as a cause of diabetes. Hyperglycemia enhances the activity of mitochondrial electron transport chain, leading to mitochondrial hyperpolarisation and elevates the reactive oxygen species (ROS) production. Increased electron availability causes partial reduction of oxygen to superoxide in the proximal electron transport chain which subsequently induces neurodegeneration in diabetes. Currently there is no satisfactory pharmacotherapy for painful diabetic neuropathy. This review summarizes mitochondrial role in type 2 diabetic neuropathy, diagnostic challenges, general treatments and benefits of alternative approach for effective management.